Multimodal constructions of gender in EFL textbooks: A critical discourse analysis from global perspective - Huda, Tanzil; Loan, Nguyen Thi Thuy; Prismantikasari, Avinia; Rachmanda, Refianisya; Aroeboesman, Fatwa Pujangga; Adhinata, Adrian Arfa (JEES (Journal of English Educators Society), 2025)
Textbooks play a pivotal role in shaping learners’ perceptions of gender norms and social identities. This study investigates how gendered identities are constructed through multimodal elements – such as text, images, and audio - in a widely used secondary - level English as a Foreign Language (EFL) textbook. Employing a qualitative methodology grounded in Critical Discourse Analysis and multimodal theory, the study reveals recurring patterns in gender representation. While some content challenges traditional stereotypes, subtle yet persistent biases remain, particularly in portrayals of occupational roles, personal agency, and gendered color schemes. Male figures are predominantly depicted as leaders or professionals, whereas female figures are more often shown in passive or domestic roles. These findings emphasize the need for critically informed revisions of educational materials to promote more inclusive, balanced, and equitable gender representations. The study contributes to global conversations on gender and education by emphasizing the importance of critical literacy in language classrooms and the role of pedagogical design in challenging entrenched gender ideologies.HIGHLIGHTS: Male characters are primarily represented in authoritative, professional, and leadershiproles, while female characters are depicted in caregiving and supportive roles. Multimodal elements (text, audio, images) largely reinforce traditional gender stereotypes,despite some use of gender-neutral language and diverse role assignments. The textbook includes selective efforts toward inclusivity, such as female environmentalactivists and gender-neutral financial scenarios, indicating a move toward balanced genderrepresentation.